Impact of proper book keeping of accounts on performance of small and medium sized enterprises (a case study in embu town) - KIBE, CAROLINE NYAMBURA (UoEm, 2024)
Small and medium sized enterprises have been witnessed that at some point their performance have been declining. Under the requirement of IFRS SMES like any other Organizations must maintain accurate books of accounts and as a result report to the same body the financial performance. The research is about the effect of effective accounting procedures on SME performance at Embu town. The research aimed at discovering the loopholes in operational of proper book keeping of accounts and try to come up the possible solution to the loophole that will be identified. Theories supporting the importance of proper book keeping includes decision usefulness theory, positive accounting theory, double entry bookkeeping theory. The research focused on SMES in Embu town, from which relevant data was collected. To achieve these objectives a survey was conducted which involved investigating SMES to get relevant information on their perception about relationship of bookkeeping and its effects on SMES. The research adhered to primary sources of data such as questionnaire and Secondary data sources was the preferred method of data collection for further analysis.